2007
DOI: 10.1158/0008-5472.can-06-2098
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Costimulation Overcomes Transforming Growth Factor-β–Mediated Repression of Proliferation of Redirected Human CD4+ and CD8+ T Cells in an Antitumor Cell Attack

Abstract: The T-cell-mediated antitumor immune response is frequently repressed in the tumor environment by an immunologic barrier, the predominant mediators of which are thought to be interleukin-10 (IL-10) and transforming growth factor-B (TGF-B). We explored the effect of these cytokines on the individual T-cell effector functions on antigen engagement during an antitumor cell attack. Isolated CD4 + and CD8 + T cells were antigen-specifically redirected toward carcinoembryonic antigen (CEA)-positive tumor cells by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 26 publications
3
60
2
Order By: Relevance
“…7 CD28-CD3z CAR signalling moreover counteracts transforming growth factor-b1-mediated repression in T-cell proliferation. 10 Both sustained survival and increased amplification result in a prolonged redirected T-cell response and in an improved antitumor attack, making second-generation CARs favorable for clinical use. [11][12][13] In physiological activation of naïve T cells, CD28 recruitment by B7 engagement sustains formation of the immunological synapse, thereby lowering the antigen threshold and increasing T-cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…7 CD28-CD3z CAR signalling moreover counteracts transforming growth factor-b1-mediated repression in T-cell proliferation. 10 Both sustained survival and increased amplification result in a prolonged redirected T-cell response and in an improved antitumor attack, making second-generation CARs favorable for clinical use. [11][12][13] In physiological activation of naïve T cells, CD28 recruitment by B7 engagement sustains formation of the immunological synapse, thereby lowering the antigen threshold and increasing T-cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…Redirected cytotoxic T cells mediate target cell lysis predominantly in a granzyme-dependent manner (11). By immunostaining tumors in mice treated with HMW-MAA redirected T cells, we thus revealed that HMW-MAA + melanoma cells took up granzyme B as did CD20 + melanoma cells after a CD20-specific T-cell attack (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…In addition, with respect to the immunosuppressive nature of the tumor milieu, TGF-, a candidate suppressive cytokine produced by tumor cells, represses the proliferation of both CD4 + and CD8 + CAR-T cell subsets but does not repress IFN- secretion of CAR-T cells or specific CAR-T cell cytolytic activity. CD28 co-stimulation overcomes the TGF--mediated repression of T-cell proliferation (Koehler et al, 2007), reflected by a more pronounced killing of tumor cells. Furthermore, in a CD28-CD3 CAR, deletion of the lymphocyte-specific protein kinase (LCK) binding site in the CD28 endodomain could improve anti-tumor activity of the CAR-T cells even though Treg cells are present in the tumor lesion (Kofler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%